Compounding in the Name of Animal Found in Rote Language of the Dengka Dialect - Efron Erwin Yohanis Loe (Universitas Airlangga, 2020)
Abstract The title of this research is compounding in the name of animal found in Rote language of the Dengka Dialect. The purpose of this research are to discover and to describe how the compounding process in the name of animal found in Rote language of the Dengka Dialect and how the structure of compounding in the name of animal found in Rote language of the Dengka Dialect. The compounding process found in the name of animal are in fowl, unfowl, and the animal of under the water. Rote language was categorized of the family of Centre Malay Polynesia and as the agglutination language. It is consist of eighteen variation dialects, namely: Termanu, Korbafo, Landu, Ringgou, Oepao, Bilba, Diu, Lelenuk, Bokai, Talae, Keka, Ba’a, Lelain, Dengka, Oenale, Dela, Tii dan Lole. One of dialects that will be analized its compounding process is Dengka dialect. The research method used is descriptive qualitative. The approach theory used to analyse the data based on the perspective of Katamba and Muslich. The structure of compound word in the name of animal found in Rote language of the Dengka dialect consists of two and three lexemes that has the same categorized and does not the same categorized. The data are obtained by using observation and interlocution method. Meanwhile the collected data techniques by using the techniques are covert in observation and interlocution methods. The techniques are covert in observation method namely: tap conversation technique, observe in conversation technique, free observe in conversation technique, writing and recording technique. The techniques are covert in interlocution method namely: stimulus technique, direct interview technique, indirect interview technique, writing and recording technique. All data were gotten from the informant. The result of data analyzed show that the compound word found in the name of animal dominated of endocentric compound. The structure of compound word construct of two and three lexemes, namely: [N+N]→[N], [N+ADJ]→[N] and [N]+[N]+[N]→[N], The compound word in the Dengka dialect was categorized as strong and permanent compound. The compound words are dominated of compound noun types. The types of compound word that found are tatpurusa and karmadharaya compound.